Bacterial Etiology of Adult Community-Acquired Pneumonia in Pakistan: A Systematic Review and Meta-Analysis - Khowaja, Rahil; Karimi, Fazila (Archives of Community Medicine and Public Health, 2025)
Background: Accurate knowledge of the epidemiology of community-acquired pneumonia (CAP) is essential for guiding appropriate antimicrobial therapy. This systematic review and meta-analysis aimed to identify and quantify the prevalence of common bacterial pathogens responsible for CAP in adult patients in Pakistan to improve empirical treatment strategies. Methods: We systematically searched EMBASE, PubMed, Web of Science, and Google Scholar for studies published in English between January 1, 2000, and December 1, 2024. Studies were included if they reported bacterial etiology of radiologically confirmed CAP in adult patients in Pakistan. Quality assessment was performed using standardized criteria, and a random-effects model was used for meta-analysis. Seven studies met the inclusion criteria, comprising 1,793 CAP patients from three major cities: Karachi (n=4 studies), Lahore (n=1), and Rawalpindi (n=1). Results: Meta-analysis revealed Streptococcus pneumoniae as the predominant pathogen (14%, 95% CI: 8-20%), followed by Pseudomonas aeruginosa (12%, 95% CI: 3-21%), Haemophilus influenzae (9%, 95% CI: 2-16%), and Staphylococcus aureus (8%, 95% CI: 2-13%). Significant heterogeneity was observed across studies (I² > 94% for all pathogens), attributable to variations in patient demographics (mean age range: 44.8-63.6 years), diagnostic methods (primarily sputum and blood cultures), and clinical settings (5 inpatient and 2 outpatient studies). Conclusion: While S. pneumoniae emerged as the leading pathogen in Pakistani adults with CAP, the high heterogeneity and limited geographic representation suggest the need for more comprehensive research. Future studies should: 1) include diverse geographic areas, particularly rural settings, 2) employ standardized diagnostic methods, and 3) investigate pathogen-specific impacts on disease severity and outcomes to enhance CAP management strategies in Pakistan.